Occupational profile in the general services sector, Los Olivos, 2025 - Castro-Hernandez, Yahaira Daleska; Mairena-Fox, Petronila Liliana (LACCEI, 2025)
Between the job profile and the interaction of its dimensions, content, context, and job profile in the general services sector in the Los Olivos district, during the period 2025. The methodology employed was a quantitative, applied approach, with a non-experimental cross-sectional design. For this purpose, a population of 385 employees in the general services sector in the Los Olivos district was used. The data collection technique was a survey, applying a 10-item questionnaire. The study showed that 49% of respondents always take courses on activities related to their position, 42% mentioned that they are sometimes informed of important aspects such as work hours, risks associated with the use of chemicals, and rotating shifts, and finally, 9% mentioned that the company never adequately informs them about the start of work activities. The conclusion is that there is interaction between the job profile and its dimensions, given that each one is collectively correlated, generating dependence, and this is statistically proven.